A Quality Assurance Framework for Strengthening Post-Certification Arabic Language Teacher Performance in Madrasah - Fathul Maujud; Syaharuddin Syaharuddin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Globally, efforts to enhance Arabic language education continue to struggle with the absence of standardized post-certification evaluation systems, and in Indonesia, this challenge is particularly evident as the lack of systematic instruments and models for assessing certified teachers undermines the long-term sustainability of professional quality. Addressing this gap, the present study was designed to develop a performance assessment instrument and a training management model within a quality-based framework that strengthens four core competencies: pedagogical, personal, social, and professional. Employing a quantitative approach, data were collected from 261 certified Arabic teachers working at MI, MTs, and MA levels across 10 districts and cities in West Nusa Tenggara Province, selected through proportionate stratified random sampling. Validation testing confirmed that the developed instrument demonstrated high validity and reliability, making it suitable for consistent use in teacher evaluation. Furthermore, performance results revealed that the majority of teachers were categorized as “very good,” indicating strong competence and positive contributions to effective, character-based learning. These findings highlight the significance of integrating systematic assessment with a continuous training model. The study suggests that adopting the proposed quality-based framework offers a sustainable pathway to enhance teacher competencies, aligning with both national education standards and Islamic educational values.